2021
DOI: 10.3892/ol.2021.12706
|View full text |Cite
|
Sign up to set email alerts
|

Stromal expression of cancer‑associated fibroblast‑related molecules, versican and lumican, is strongly associated with worse relapse‑free and overall survival times in patients with esophageal squamous cell carcinoma

Abstract: Cancer-associated fibroblasts (CAFs) in the tumor microenvironment play an essential role in the tumor progression of esophageal squamous cell carcinoma (ESCC). The present study aimed to investigate the expression of CAF-related molecules, versican, periostin and lumican, in cancer stroma, to provide prognostic stratification for patients with ESCC after surgery. A total of 106 patients with ESCC who underwent curative esophagectomy without preoperative chemotherapy or radiotherapy were enrolled. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Previous studies showed that VCAN was closely associated with the proliferation and metastasis of various types of tumor cells, such as gastric cancer, leukaemia and breast cancer cells 40 42 . In addition, a recent study showed that stromal expression of VCAN was strongly associated with worse overall and relapse-free survival in patients with ESCC 43 . The ROC curves showed that all 9 hub genes had relatively high diagnostic value for ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that VCAN was closely associated with the proliferation and metastasis of various types of tumor cells, such as gastric cancer, leukaemia and breast cancer cells 40 42 . In addition, a recent study showed that stromal expression of VCAN was strongly associated with worse overall and relapse-free survival in patients with ESCC 43 . The ROC curves showed that all 9 hub genes had relatively high diagnostic value for ESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have demonstrated using VCAN-negative QRsP11 fibrosarcoma cells that VCAN is an important molecule in functional ECM and maintenance of cancer-associated fibroblasts (Fanhchaksai et al, 2016). In addition to this, the high expression levels of CAF-related molecules including VCAN, periostin, and lumican in the stroma of ESCC were significantly associated with worse recurrence-free survival (RFS) and overall survival in ESCC patients (Yamauchi et al, 2021). In addition, TGF-β enhances ovarian cancer cell invasiveness by up-regulating VCAN in CAFs.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, high stromal periostin expression was significantly associated with high budding in UTUCs. Several studies have also indicated a close relationship between stromal periostin overexpression and histological small clustering and/or isolated invasive patterns of cancer cells at the tumor front, such as tumor budding in colorectal adenocarcinoma [ 35 ] and “pattern of invasion” in oral squamous cell carcinoma [ 36 ]. Overexpression of periostin co-localizes with fibronectin and collagen, thereby promoting an extracellular matrix organization through the activation of focal adhesion kinase and PI3K/Akt signaling [ 13 ].…”
Section: Discussionmentioning
confidence: 99%